The Role of International Standards for Project Management in Increasing Project Quality in Application to International Partnerships in the kingdom of Saudi Arabia (International Journal of Financial, Administrative and Economic Sciences, 2024)
The study aimed at determining the impact of projects and the extent of its international project management standards, which helps to achieve the quality of the project as a competitive advantage indicator. And to identify the role of international standards for project management and its impact on increasing project quality in international institutions in Saudi Arabia. The research was adopted on the descriptive approach, which depends on the phenomenon and analyzes, and take advantage of the various phenomena to reach the generalization and modifications of the study community and adopted the study on the questionnaire as a student. The success of the project is primarily depending on an effective management and monitoring of all activities for the project
Keywords: International Standards for Project Management; Project Quality; International Companies